2006
DOI: 10.1186/1465-9921-7-107
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of neonates to Respiratory Syncytial Virus is critical in determining subsequent airway response in adults

Abstract: Neonatal RSV exposure results in long term pulmonary inflammation and exacerbates allergic airways disease. The early increase in TNF-alpha in the bronchoalveolar lavage implicates this inflammatory cytokine in orchestrating these events. Finally, the data presented emphasize IL-13 and TNF-alpha as potential therapeutic targets for treating RSV induced-asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 29 publications
(34 reference statements)
7
111
0
2
Order By: Relevance
“…Neutrophils respond to TNF-a with a respiratory burst after a b 2 -integrin-dependent adherence to extracellular matrix proteins (Decleva et al, 2002). TNF-a has been proposed as an ideal drug target for the therapy of RSVinduced bronchiolitis (Rutigliano & Graham, 2004;You et al, 2006). Overall, our study points to a role for innate immunity in RSV disease, a conclusion that was also drawn from a genetic-association study in children (Janssen et al, 2007).…”
Section: A F G Antonis and Otherssupporting
confidence: 67%
See 1 more Smart Citation
“…Neutrophils respond to TNF-a with a respiratory burst after a b 2 -integrin-dependent adherence to extracellular matrix proteins (Decleva et al, 2002). TNF-a has been proposed as an ideal drug target for the therapy of RSVinduced bronchiolitis (Rutigliano & Graham, 2004;You et al, 2006). Overall, our study points to a role for innate immunity in RSV disease, a conclusion that was also drawn from a genetic-association study in children (Janssen et al, 2007).…”
Section: A F G Antonis and Otherssupporting
confidence: 67%
“…However, when in excess, TNF-a can provoke chronic inflammatory disorders. You et al (2006) recently published the results of a study in a neonatal-mouse model and suggested that TNF-a plays a key role in mediating chronic inflammation (e.g. asthma) of the bronchi after RSV infection.…”
Section: A F G Antonis and Othersmentioning
confidence: 99%
“…Finally, rodent models suggest that respiratory viral infections of immature and mature animals (90) result in chronic pathologic changes in the lung, airway hyperreactivity, and immune system changes similar to those seen in human asthma (98)(99)(100)(101). In addition, these early-life infections may alter subsequent responses to viral infection in adult animals (102,103).…”
Section: Biologic Mechanisms Through Which Respiratory Viral Infectiomentioning
confidence: 99%
“…26 In se ve ral stu di es, it was shown that IL-4, IL-13 and IFN-γ le vels in cre a sed af ter RSV in fec tion. [27][28][29] However no re la ti on was shown bet we en IL-4, IFN-γ le vels and re cur rent whe e zing epi sodes. 30 In our study, IL-13 levels were not dif fe rent in RSV po si ti ve and ne ga ti ve ca ses but IL-4 and IFN-γ le vels we re sig ni fi cantly hig her in the non-RSV gro up.…”
Section: Discussionmentioning
confidence: 99%